Tenacidade à fratura de liga de alumínio formadora de fase quasicristalina fabricada por manufatura aditiva - Rocha, Erlifas Moreira (2024)
Recent studies have demonstrated the feasibility of obtaining a metastable quasicrystalline phase in Al-Fe-Cr-Ti alloys through Laser Powder Bed Fusion (L - PBF). These alloys are promising for use in matrices and structural components due to their high specific strength and wear resistance, especially at high temperatures. Although the fracture toughness of these alloys has not been previously studied due to the difficulty of manufacturing bulky parts by traditional methods, they are expected to exhibit high toughness due to their microstructure, which combines a nanometric, high-strength quasicrystalline phase with a spherical morphology in a dendritic aluminum matrix refined by the high cooling rates of the L-PBF process (≈10^5 K/s). This project investigated the fracture toughness of the recycled Al95Fe2Cr2Ti1 alloy produced by L-PBF. The powders were produced by gas atomization, characterized, and used in the L - PBF process. After optimizing the parameters, samples were fabricated in different build directions, with some subjected to heat treatments. Fracture toughness was evaluated using the KIC technique, according to ASTM E399 standards. The results showed that fracture toughness is sensitive to build direction and heat treatments. The 0° build direction without heat treatment exhibited the best results, with values exceeding 34 MPa·√, followed by 29 MPa·√ and 26 MPa·√ for stress relief and quasicrystalline phase (QC) decomposition treatments, respectively. These values are comparable to AlSi10Mg, AlSi7Mg, and 2XXX series alloys, such as 2024, produced by L-PBF. Regarding fracture mechanisms, for samples built at 0°, cracks propagated through the edges of the melt pools. For samples built at 45°, cracks followed a stepped propagation along the edges of the melt pool. In the 90° build samples, the fracture exhibited a mixed behavior, with propagation through both the center and edges of the melt pools, indicating a relationship between the load and the build direction.